STUDENT PERSPECTIVE GAP BETWEEN ENTREPRENEURSHIP GOALS AND ENTREPRENEURSHIP DISINTEREST - Atirah Atirah (Institut Agama Islam Muhammadiyah Sinjai, 2023)
The college period is a time where every student will find their identity and try to grow and adapt to the campus environment. At that time, students should be able to explore themselves to continue to develop not only in the majors that have been chosen but also to be able to see the career opportunities that exist in addition to the majors that have been chosen.This study aims to look at the gaps in students' perspectives regarding the goals of entrepreneurship with disinterest in entrepreneurship. This study uses a descriptive qualitative research type where to draw conclusions from the results of the study, the researcher asks the same questions to the informants to see the uniformity of perspectives obtained from the interviews and then describes the results of the interviews and draws conclusions. The informants in this study were students who had followed the Entrepreneurship Course by running the Entrepreneurial Learning Experience Practice.The results of student research assume that the purpose of entrepreneurship is to provide career options and help earn income but still after taking courses with entrepreneurship learning experience assignments. Students also have not found their interest in entrepreneurship in college for a simple reason. to do other coursework